In-situ acceleration-speed profile of an elite soccer academy: A cross-sectional study - Cardoso, P.; Tavares, F.; Loureiro, N.; Ferreira, R.; Araújo, J. P.; Reis, J.; Vaz, J. R. (Journal of Sports Sciences, 2023)
Speed is an essential skill in sports performance and an important performance metric in talent identification. This study aims to evaluate and compare the sprint acceleration characteristics across different age groups in an elite soccer academy. A total of 141 elite academy soccer players were recruited to participate in the study, and they were assigned to their respective competitive age groups, ranging from under-14 to the B-team. An individual in-situ acceleration-speed (A-S) profile was assessed and derived from Global Position System (GPS) speed-acceleration raw data, from 10 consecutive football sessions, in the beginning of the season. The results showed that under-14 players exhibited significantly lower theoretical maximum speed (S0) (np^2 = 0.215, p < 0.01) when compared with all other age groups. However, no differences were found between maximum theoretical acceleration (A0) and A-S slope between age groups. The results suggest that sprint mechanical profiles of young soccer athletes remain stable throughout their athletic development. Nevertheless, younger athletes have less capacity to apply horizontal force at higher speeds (S0).